2019
DOI: 10.3390/atmos10110705
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Reference Evapotranspiration over Southwest China during 1960–2018: Attributions and Implications for Drought

Abstract: Reference evapotranspiration (ET0) is important to the global energy balance and to hydrological cycling. However, the extent to which ET0 changes, the main driving factors, and especially the implications of its shift for drought in Southwest China are not clear. In this study, trends in Penman–Monteith ET0 and other climatic parameters at 79 stations in Southwest China from 1960 to 2018 were investigated by using the Mann–Kendall test. Furthermore, partial correlation analysis and multiple linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 83 publications
3
13
0
Order By: Relevance
“…Overall, wind speed is the only variable that decreases significantly on an annual scale and during the rainy period. Similar results have been obtained by Zeng et al [69] who observed a significant decrease in wind speed during the period 1960-2018 in southwest China. In addition, Oguntunde et al [70] also found a significant decrease in wind speed over the 1973-2008 period in Nigeria.…”
Section: Climate Zonessupporting
confidence: 91%
“…Overall, wind speed is the only variable that decreases significantly on an annual scale and during the rainy period. Similar results have been obtained by Zeng et al [69] who observed a significant decrease in wind speed during the period 1960-2018 in southwest China. In addition, Oguntunde et al [70] also found a significant decrease in wind speed over the 1973-2008 period in Nigeria.…”
Section: Climate Zonessupporting
confidence: 91%
“…(Liu et al 2017) found out that wind speed did not have signi cant effect on the ET 0 values at the stations of Yellow River catchment which supports the results obtained by the current work. A past research (Zeng et al 2019) found that wind speed decreased for most of the 79 stations of south west China on the entire study duration and had very minor contribution to the variations of annual ET 0 values, which again is in accordance with the outcomes of the existing work.…”
Section: Trend Of Wind Speedsupporting
confidence: 89%
“…Feng and Fu (2013) considered the rising temperature as the main reason of global drought. Zeng et al (2019) attributed the spring and winter drought to a decrease in relative humidity which led to an increase in reference evapotranspiration, while the duration of sunshine was the dominant factor of summer and autumn drought in southwest China from 1960 to 2000. In addition, soil drought (low soil moisture) and atmospheric aridity (high vapor pressure deficit, VPD) have been regarded as the two main factors responsible for drought, which influenced terrestrial water use and carbon uptake further (Novick et al, 2016;Zhou et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%